Light management with quantum nanostructured dots-in-host semiconductors - M. Alexandre (Nature Publishing Group, 2021)
Development of a simple yet insightful model to understand the optical behavior of dots-in-host semiconductors. Unprecedentedly shown that quantum-enabled absorption coefficients can reach levels close to that of bulk semiconductors.